Protective effect of baicalin on oxidative stress injury in retinal ganglion cells through the JAK/STAT signaling pathway in vitro and in vivo - Yu, Huan; Zhou, Dan; Wang, Wei; Wang, Qingxia; Li, Min; Ma, Xiaoyun (Frontiers in Pharmacology, 2024)
Background and Purpose: The damage or apoptosis of retinal ganglion cells (RGCs) is one of the leading causes of various blinding eye diseases, such as glaucoma, diabetic retinopathy, optic neuritis, and ischemic optic neuropathy. Oxidative stress is involved in RGC death. Baicalin, a flavonoid compound extracted from Scutellaria baicalensis, has various beneficial effects, including anti-inflammatory, anti-apoptotic, and antioxidant properties. However, the effects of baicalin on RGCs and the underlying mechanisms require further investigation. Methods: In this study, a glutamate-induced oxidative stress damage model of R28 cells and a rat retinal injury model were established to investigate the effects of baicalin on oxidative stress damage to RGCs and try to elucidate the underlying mechanism. Results: In vitro experiments demonstrated that the survival rate of R28 cells after glutamate treatment dropped to 33.4%, while 10 μM baicalin significantly inhibited glutamate-induced damage in RGCs (P<0.001) and enhanced cell viability through decreasing ROS levels, increasing antioxidant enzyme activity, and suppressing the expression of inflammatory factors iNOS, TNF-α, IL-6, and IL-1β (P<0.001). In vivo, baicalin effectively mitigated structural damage to retinal tissue and RGC morphology induced by glutamate, increasing the thickness of the retinal ganglion cell layer, improving RGC density, and reducing overall retinal thinning in rats (P<0.001) in a time- and dose-dependent effects. Mechanistic studies revealed that glutamate evaluated the phosphorylation levels of JAK/STAT, while baicalin effectively inhibited the activation of the JAK/STAT signaling pathway. Conclusion: This study confirmed that baicalin protects against glutamate-induced oxidative stress damage in RGCs. It effectively alleviates oxidative stress and inflammatory responses, reduces cell apoptosis, and improves the pathological changes in the retina of rat models of RGCs damage, thereby decreasing RGC death. Further exploration of its mechanism revealed that baicalin effectively inhibits the JAK/STAT signaling pathway, protecting RGCs from oxidative stress damage. This provides an experimental basis for the application of baicalin in the treatment of RGCs damage.